Hemoperitoneum due to deep endometriosis in a patient on peritoneal dialysis with a good response to progestin - Monich, Aline Grosskopf; Carneiro, João Luis dos Santos; Gevert, Felipe; Romani, Rafael Fernandes (Brazilian Journal of Case Reports, 2023)
Hemoperitoneum is common in patients undergoing peritoneal dialysis. Its varied causes include catheter-related complications, obstetric and gynecological etiologies, coagulopathies, and vascular, infectious, and intra-abdominal pathologies. A gynecological etiology, whether pathological or physiological, is the most common cause of hemoperitoneum in adult women undergoing peritoneal dialysis, with more than one-third of cases related to the menstrual cycle. Endometriosis can also cause hemoperitoneum, and the bleeding may originate from endometrial tissue implanted in the peritoneal cavity or that detaches from the intrauterine endometrium during the menstrual period. We report a case of hemoperitoneum in a patient with deep endometriosis and previous hysterectomy who had an excellent response to oral progestin.